Spillover effect of workplace democracy: A conceptual revision - Rybnikova, Irma (Frontiers in Psychology, 2022)
The so-called "spillover thesis” by Pateman is one of the prominent theoretical explanations for why workplace-based participation and democracy could induce stronger political participation. By this thesis, Pateman underscores the relevance of industrial workplaces as relevant places where citizens can be socialized regarding democratic attitudes while proposing the educative effect of workplace democracy and assuming a strong linkage between workplace-based and political participation as moderated by self-efficacy. The spillover thesis receives a controversial consideration as empirical studies provide inconsistent evidence so far. Some empirical undertakings support the assumption by Pateman and indicate a positive relationship between workplace democracy and societal effects, like increased moral and community orientation or higher levels of political participation among employees from companies with higher degrees of workplace democracy. Other empirical studies yield results that do not confirm the thesis. Scholars have already discussed method-based shortcomings of the previous empirical research while pointing to the inconsistency of definitions and operationalizations as the main shortcoming (e.g. Kim 2021). In difference to that, systematic conceptual consideration of the spillover thesis and the accompanying scholarship is still missing. The present paper addresses this shortcoming and provides a critical reflection on the spillover thesis and corresponding research. It aims at identifying the main conceptual shortcomings and to provide avenues for future theoretical undertakings in analyzing whether and how participation at the workplace is related to participation in political domains.